Nursing Leadership Practices Among Nurse Managers in the Kumasi Metropolitan Area: An Exploratory Descriptive Qualitative Study - Emmanuel Obromah Amoh‐Kusi; Prosper Manu Abdulai; Collins Atta Poku; Victoria Bam (Nursing Open, 2026)
ABSTRACT Aim To explore nurse managers' perceptions of how leadership practices contribute to the work environment within selected healthcare facilities in Ghana. Design An exploratory descriptive qualitative design was employed to gain an in‐depth understanding of nurse managers' leadership experiences. Methods Nineteen nurse managers with at least 2 years of managerial experience from three healthcare facilities in the Kumasi Metropolitan Area were purposively selected to participate in the study. Data were collected through semi‐structured in‐depth interviews and were analysed using thematic analysis. Results Findings revealed that nurse managers commonly adopted a mixed (situational) leadership approach, adapting their leadership behaviours to meet varying workplace demands. Other leadership styles, including transformational, transactional, democratic, and laissez‐faire, were also reported. Effective communication, staff mentorship, and participatory decision‐making and supportive supervision emerged as key leadership practices that fostered a healthy work environment. Participants also identified organisational support, adequate staffing, and professional development opportunities as important enablers of effective leadership. Conclusion Nurse managers described flexible, context‐responsive leadership practices involving supervision, communication, mentorship, participatory decision‐making, motivation, and adaptation to organisational demands. Participants perceived these practices as relevant to the nursing work environment, while staffing constraints, workload, resource limitations, and organisational structures were described as contextual challenges. Because the study reflects nurse managers' perceptions, the findings do not establish causal effects on staff retention, job satisfaction, workforce performance, or patient outcomes. Implications for Nursing Practice Leadership education, structured mentorship, adequate staffing, and supportive organisational systems may be considered as potential areas for intervention and should be evaluated for feasibility and effectiveness in future implementation studies. No Patient or Public Contribution No patient or public involvement in this study.